Direct evaluation of free energy for large system through structure integration approach. (8th September 2015) - Takeuchi, Kazuhito; Tanaka, Ryohei; Yuge, Koretaka
Abstract: We propose a new approach, 'structure integration', enabling direct evaluation of configurational free energy for large systems. The present approach is based on the statistical information of lattice. Through first-principles-based simulation, we find that the present method evaluates configurational free energy accurately in disorder states above critical temperature.